Mob Family Proteins: Regulatory Partners in Hippo and Hippo-Like Intracellular Signaling Pathways - Duhart, Juan Carlos; Raftery, Laurel A. (Frontiers in Cell and Developmental Biology, 2020)
Studies in yeast first delineated the function of Mob proteins in kinase pathways that regulate cell division and shape; in multicellular eukaryotes Mobs are essential for regulation of tissue growth and morphogenesis. In animals, Mobs are adaptors in Hippo signaling, an intracellular signal-transduction pathway that restricts growth in epithelial tissues, impacting the development and homeostasis of animal organs. Central to Hippo signaling are the Nuclear Dbf2-Related (NDR) kinases, Warts and LATS1 and LATS2, in flies and mammals respectively. A second Hippo-like signaling pathway that regulates cell and tissue morphogenesis has been uncovered that is similarly conserved. Central to this emergent pathway are the NDR kinases, Tricornered and STK38 and STK38L. Hippo-like kinase activation of NDR kinases requires a minimum of three direct regulatory inputs by a conserved set of co-activating proteins. This review focuses on one co-activator family, the highly conserved, non-catalytic Mps1-binder-related (Mob) proteins. Mobs are allosteric activators of NDR kinases and adaptors that contribute to assembly of multiprotein NDR kinase activation complexes. In multicellular eukaryotes, the Mob family has expanded relative to model unicellular yeasts; accumulating evidence points to Mob functional diversification. A striking example comes from the most sequence-divergent class of Mobs, which are components of the highly conserved Striatin Interacting Phosphatase and Kinase (STRIPAK) complex, that antagonizes Hippo signaling. Mobs stand out as critical regulators of NDR kinase activity that both directly contribute to activating NDR kinases and indirectly to antagonize NDR kinase activation, thus modulating the output from Hippo and Hippo-like kinases. These opposing Mob functions raise the possibility that they coordinate the relative activities of the Tricornered/STK38/STK38L and Warts/LATS kinases. We survey the different facets of Mob-dependent regulation of Hippo and Hippo-like signaling and highlight open questions that hinge on unresolved aspects of Mob functions.